Development of a Problem-Based Physics Teaching Module to Enhance Students’ Science Process Skills - Hasanah, Rabiatul; Gunawan, Gunawan; Muntari, Muntari; Rokhmat, Joni; Harjono, Ahmad (Department of Physics Education, Universitas Mataram, 2025)
This study aims to develop a valid, practical, and effective problem-based physics teaching module to enhance students’ science process skills (SPS). The research employs a Research and Development (R&D) approach using the 4D development model, which includes the stages of Define, Design, Develop, and Disseminate—limited in this case to dissemination among physics teachers. The Develop stage involved the creation of the teaching module as well as validation, practicality, and effectiveness testing. The module was evaluated by three expert validators to assess its validity. Practicality was measured through student and teacher responses and the implementation of the learning process, involving 18 students from Class XI IPA 1 at a high school in Pringgabaya District. Effectiveness testing used a one-group pretest-posttest design and included 36 students from Classes XI IPA 2 and 3 at the same school. Data collection instruments included validation sheets, teacher and student response questionnaires, lesson implementation observation sheets, and SPS questionnaires. Data were analyzed using Aiken’s V index, percentage calculations, and the N-Gain test. The validation results showed that both the module and instruments had average validity ratings categorized as